Pembekalan Guru Kristen dalam Integrasi Teologi terhadap Pembelajaran Melalui Yayasan Amarta Kasih Indonesia - Neneng Andriani; Chandra Han; Wiputra Cendana (JURNAL ComunitÃ Servizio : Jurnal Terkait Kegiatan Pengabdian kepada Masyarakat, terkhusus bidang Teknologi, Kewirausahaan dan Sosial Kemasyarakatan, 2025)
Christian schools are partners with God who are called as servants in the educational mission to teach the truth about God. SMA Kristen 1 Surakarta is one of four private Christian high schools in Surakarta, with the hope that the school can guide and lead students to true, Bible-based teachings and glorify God. However, most Christian teachers still have difficulties integrating biblical Christian worldview into their learning and life. Christian ministry with sustainable activity programs needs to be carried out by providing guidance, training, and coaching for teachers. The implementation method is carried out through 3 stages, namely: 1) pre-implementation, which carried out with situation analysis and activity program planning in collaboration with partners; 2) implementation is carried out with 3 times session for teachers and staffs, offline and online; and 3) post-implementation, which are evaluation and follow-up plan. The expectation is that SMA Kristen 1 Surakarta will have the capital to carry out Christian faith-based learning that is biblical and in line with the government curriculum. The results and impact of this community service (PkM) activity are useful for teachers to develop true Christian learning which can be seen from the survey results after the training held. The conclusion is that this PkM has succeeded in having a positive impact on teachers in understanding Christian education to be able to develop correct Christian learning. Thus, this PkM activity will continue to be carried out sustainably in the next academic year targeting training and practical guidance in implementing Christian worldview in teaching and learning.